Editorial Foreword: IKAT on the Right Track - David Robie (Center for Southeast Asian Social Studies (CESASS), 2018)
This is the second edition of IKAT: The Indonesian Journal of Southeast Asian Studies and I have been honoured with a request to write an editorial foreword for this welcome addition to global research publishing with a focus on a region facing important challenges and interesting times. I thank Dr. phil. Hermin Indah Wahyuni, Dr. Vissia Ita Yulianto and her editorial colleagues for the invitation and opportunity to collaborate with this quality research initiative. The Center of Southeast Asian Social Studies (CESASS) at the Universitas Gadjah Mada, Yogyakarta, Indonesia, must be commended for launching such a valuable publication. The Pacific Media Centre at Aotearoa/New Zealand’s Auckland University of Technology (AUT) is proud to be associated with the venture.